Nodal metastases from laryngeal carcinoma and their correlation with certain characteristics of the primary tumor - Kaur, Kamaljit (Springer India, 2002)
5O cases of carcinoma larynx were included in a prospective study to detect the incidence and pattern of nodal metastases (both clinical and occult) and to study the influence of certain characteristics of the primary tumor on the incidence of nodal metastases. In our study 66% (33 cases) of the lesions were transglottic as compared to 24% (12 cases) supraglottic and 10% (5 cases) glottic lesions. The most common age group affected in our study was 51-60 years comprising 50% of the cases. The most common symptoms were hoarseness, breathlessness and difficulty in swallowing. The incidence of clinically positive neck at the time of presentation was 42% while the incidence of occult nodal metastases was found to be 27.6%. The most common levels of lymph nodes involved in our study were levels II and III (87.5% cases). Multiple level lymph node involvement was seen in 71.4% of the eases at the time of presentation. A high incidence of cervical nodal metastases was associated with the following characteristics of the primary lesion-extralaryngeal spread, infiltrating or endophytic peripheral growth pattern, poor cellular differentiation and advanced T stage. In view of the high incidence of occult nodal metastases, use of selective lateral neck dissection is advocated in patients with a clinically negative neck at the-time of presentation (early glottic carcinomas being excluded).